Kajian Pengembangan Produk Wisata Alam Berbasis Ekologi di Wilayah Wana Wisata Curug Cilember (WWCC), Kabupaten Bogor - Qurie Purnamasari; Andry Indrawan; EKS Harini Muntasib (Jurnal Manajemen Hutan Tropika, 2005)
Recreation development is usually oriented toward on the mass tourism to maximise a number of tourists and rarely put the environmental aspect into consideration.  This created an effect on the sustainability of ecology.  This study’s emphasis is on figuring out an alternative of outdoor recreation product which based on the ecology aspect to support the development of outdoor recreation in the Wana Wisata Curug Cilember (WWCC). This study put the characteristic of tourist and local people into consideration which are describe the product of ecology recreation in order to achieve an ideal product that has not been reached previously and still need more serious effort.  Analysis descriptive with qualitative and quantitative approach is used in this study.  SWOT (Strengths, Weaknesses, Opportunities, Threats) and descriptive statistic are considered for alternative outdoor recreation product while the AHP (Analysis Hierarchy Process) has been  used to achieve a priority product for implementation.  The findings suggested a diversification strategy or S-T (Strengths – Threats) was chosen to develop the products of recreation in WWCC.  The priority of these products based on the AHP value are as follows: a) Water falls (0.2700), b) Natural scenery (0.1623), c) Camping (0.1405), d) Hiking (0.1073), e) Theraphy of water fall energy (0.0885),  f) Plants viewing (0.0665), g) Wildlife viewing (0.0525) and h) Outbound (0.0380).